Analysis of classical flutter in steam turbine blades using reduced order aeroelastic model - Prasad Chandra Shekhar; Pešek Luděk (MATEC Web of Conferences, 2018)
In the present paper classical flutter phenomena in LP steam turbine rotor is studied . A reduced order aeroelastic model (ROAM) with acceptable accuracy and fast execution is developed for this purpose. The aerodynamics damping (AD) is estimated using Traveling wave mode (TWM) method. Flow field is modeled using Panel method. For the structural part ROM non-linear beam element method (BEM) based FEM structural solver is used. Partitioned based ( loose) coupling approach is adopted to perform aeroelastic (flutter) cosimulation. Both 2D cascade flow and 3D cascade are modeled.The estimated stability parameters are compared with experimental data. Moreover, present ROAM shows significant reduction in computational time.